¡Y Barbie cumpló 40 años! (Journal of Parents and Teachers, 2014)
The article takes a journey through the process of creating Barbie. In this way, it details the previous ideas and all those aspects that characterise both her family and her body image. It also includes activities related to Barbie to be carried out in the classroom, introducing questions that guide the dialogue between the students and the teacher.
Keywords: Barbie; Reflection; Toys; Dynamics